PENDAMPINGAN EVALUASI RUMUSAN CAPAIAN PEMBELAJARAN LULUSAN (CPL) BEBERAPA PROGRAM STUDI S1 FARMASI - Azis Saifudin (LPPM Universitas Bina Bangsa, 2024)
Tremendous growth in the number of undergraduate pharmacy programs in Indonesia between 2015 and 2020 has resulted in incapacities in many aspects of institutions, in particular academic staff numbers, educational supporting facilities and infrastructure quality, and curriculum design capability to fulfill the outcome-based education (OBE) era in Indonesia. Even in the initial stage, creating program learning outcomes (PLO) is becoming a hurdle in many pharmacy study programs. On the other hand, a firm PLO formulation of a study program will propel many downstream aspects in the educational management cycles. Based on several PLOs designing supervision, it can be revealed that some competence leveling statements, standardization according to higher education order, and wording choices are critical. Based on the real experience, in this review, the inaccuracies in PLO arrangements will be defined and clarified